Labyrinths, intellectuals and the revolution : the Arabic-language Moroccan novel, 1957-72 - Campbell, Ian, 1967- (Studies in the History and Society of the Maghrib, 2013)
Labyrinths, Intellectuals and the Revolution traces the development of the postcolonial Arabic-language Moroccan novel from its roots in travel narratives and autobiography into its more mature period of stylistic and thematic diversity in the early 1970s. This study first undertakes an exploration of the political, social and artistic conditions under which the genre developed, then moves to close readings of each of the formative texts, grouped by theme. The analysis of these texts centers around their spatial practices: there is a tension between the labyrinthine space of the street, which deflects legibility, and the sacred interior within the blank walls, wherein a certain equality of gaze and power can be perceived.